Comparative study of religious spirituality and intellectual spirituality; Emphasizing Mr. Malekian's theory of rationality and spirituality - sayyedsajjad jafari; mahdi nemati (پژوهش‌نامه کلام تطبیقی شیعه, 2023)
One of the important topics related to religion is its connection with rationality, around which various views have been raised; As today, a group of people talk about pure rationalism as an independent criterion for distinguishing between right and wrong, for this reason, the present study seeks to answer the question, to what extent the theory of rationality can be a suitable criterion for answering, with a comparative study of religious spirituality and rational spirituality. And replace religious spirituality? The research method is analytical-descriptive and data collection has been done using library resources. After examining the origin of rationalized religion, the basics and characteristics of the said topic were discussed and finally the shortcomings of rationalized religion were discussed. The results of the research have shown that rationalized religion relies on the foundations and features such as secularism and humanism... based on which it suffers from deficiencies such as: the lack of clarity in the definition of rationalized religion, failure to achieve the goals of the theory, and contradictions in the nature of faith. ...it has happened that in many cases, not only can it not be a gift for modern man; It has also led to pain and suffering.